Non-material considerations and uniqueness in the planning of the development of urban space: Example of Lviv - Musiaka, Łukasz; Habrel, Mykola; Habrel, Mykhailo; Kosmiy, Myhailo (European Spatial Research and Policy, 2021)
The paper is an attempt to respond to selected problems of the spatial planning system in Lviv, as defined by analyses of strategic documents. Based on the analysis, the authors proposed a spatial planning model considering non-material and hard-to-measure factors which have shaped the city. Lviv was selected for analysis because of its size, its long and multicultural history, and its considerable accumulation of tangible and intangible cultural heritage elements from various eras. Today, the city faces numerous challenges in terms of heritage protection, its functional and spatial development, and the choice of an effective form of planning and management. Hence the need to offer an in-depth reflection on the importance and to consider the rich cultural heritage and non-material factors shaping urban space, in the spatial planning process.